Creative Projects Based on the Ruang Belajar (Rubel) Application in Islamic Religious Education Learning - Putri Enti Rahayu; Nur Jannah (IQRO: Journal of Islamic Education, 2026)
Islamic Religious Education (PAI) learning still faces challenges in increasing student participation and creativity due to the teacher-centered learning model. One effort that can be done is implementing digital technology-based creative projects. SMAN 1 Yosowilangun developed the Ruang Belajar (Rubel) application as a platform to support such learning. This study aims to describe the implementation of Rubel-based creative projects in PAI learning and identify the forms of creative projects developed. The study used a qualitative approach with a case study type involving the Vice Principal for Curriculum, PAI teachers, and students. Data were obtained through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that the implementation of Rubel-based creative projects was carried out through the planning, implementation, and evaluation stages. The resulting projects included videos, infographics, and digital posters that contributed to increasing student participation, creativity, collaboration, digital literacy, and understanding through more active, contextual, and student-centered learning.